Barbastella barbastellus ... - Don E. Wilson; Russell A. Mittermeier (Lynx Edicions, 2019)
219. Western Barbastelle Barbastella barbastellus French: Barbastelle d'Europe / German: Mopsfledermaus / Spanish: Barbastela Other comesnon names: Barbastelle Taxonomy. Vespertilio barbastellus Schreber, 1774, Burgundy, France. Two subspecies are recognized. Subspecies and Distribution. B.b.barbastellusSchreber,1774—EuropefromIrelandandIberianPeninsulaEtoLaivia,Belarus,Ukraine,andtheCauca-sus;alsomajorMediterraneanIs,Moroc-co,andTurkey(Anatolia);possiblyextinctinBelgium,Netherlands,andNorway. B. b. guanchae Trujillo, Ibanez & Juste, 2002 — Canary Is (Tenerife and La Gomera). Descriptive notes. Head-body 45-60 mm, tail 36-52 mm, ear 12-18 mm, forearm 35-43 mm; weight 5-14 g. Females slightly larger than males; body slender. Fur is long, silky, and black-brown, frosted with white or yellowish-golden tips. Skin dark brown or grey. Juvenile much darker than adult. Ears have distinctive flap of skin (c.5-6 transverse folds) on outer edge; tragus triangular and very distinctive, tapering very abruptly to end ... : Published as part of Don E. Wilson & Russell A. Mittermeier, 2019, Vespertilionidae, pp. 716-981 in Handbook of the Mammals of the World – Volume 9 Bats, Barcelona :Lynx Edicions on pages 860-861, DOI: 10.5281/zenodo.6397752 ...